Research of Driving Circuit in Coaxial Induction Coilgun - Yadong Zhang; Jiangjun Ruan; Yuanchao Hu Yuanchao Hu; Ruohan Gong; Weijie Zhang; Kaipei Liu (Universitas Ahmad Dahlan, 2013)
Power supply is crucial equipment in coaxial induction coil launcher. Configuration of the driving circuit directly influences the efficiency of the coil launcher.This paper gives a detailed analysis of the properties of the driving circuit construction based on the capacitor source. Three topologies of the driving circuit are compared including oscillation, crowbar and half-wave circuits. It is proved that which circuit has the better efficiency depends on the detailed parameters of the experiment, especially the crowbar resistance. Crowbar resistor regulates not only efficiency of the system, but also temperature rise of the coil. Electromagnetic force (EMF) applied on the armature will be another problem which influences service condition of the driving circuits. Oscillation and crowbar circuits should be applied to both of the synchronous and asynchronous induction coil launchers, respectively. Half-wave circuit is seldom used in the experiment. Although efficiency of the half-wave circuit is very high, the speed of the armature is low. A simple independent half-wave circuit is proposed in this paper. In general, the comprehensive property of crowbar circuit is the most practical in the three typical circuits. Conclusions of the paper could provide guidelines for practice.